Effects of Oral Zinc Supplementation on Early Embryonic Development and Neonates of Aged Female Albino Mice - Al-Rudaini, Amjed T.; Salih, Lina A.; Al-Dujaily, Saad S. (Iraqi Journal of Science, 2024)
Female reproductive aging is a normal phase of life that eventually leads to menopause and reproductive senescence. The current experimental investigation was intended to study zinc supplementation effects on early embryonic development and neonates in 26-28 weeks old female mice. In this investigation, 80 mature female mice were used that were divided into two groups of forty each. Two control groups received distilled water, while two Zn groups were given 0.115 mg/kg/day Zn orally daily during 2-3 estrous cycles. The female mice were all mated with adult males. Twenty female mice from both the control and Zn groups were euthanized by CO2 gas inhalation, and then a longitudinal incision in the abdomen of each female mouse was performed and uterine horns and oviducts were detached from the body in order to obtain two-cell embryos. On the other hand, 20 pregnant mice from each group were permitted to complete their pregnancy until birth and then their neonates were collected for macroscopic examination. The findings showed that the Zn supplementation significantly (P≤0.01) improved the mean embryonic development and the quality of 2-cell stage embryo grade A. Whereas, it decreased the mean embryonic development of 2-cell stage embryo grade D in aged female mice significantly (P≤0.01) in comparison with aged control groups. Also, the count and quality of neonates from Zn-treated aged female mice enhanced significantly (P≤0.01) as compared to non-treated aged female mice. It was concluded from these findings that the Zn can improve embryonic development and neonate count and quality in aged mice.